2022
DOI: 10.1007/s10508-022-02354-z
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Screening Scale of Pedophilic Crime Scene Behavior

Abstract: The Screening Scale of Pedophilic Crime Scene Behavior (SSPC) is a seven-item structured rating scale assessing pedophilic sexual arousal. In the current study, we cross-validated the scale’s convergent validity using multiple measures of sexual interest in children (clinical diagnosis of pedophilia, the high fixation/low social competence type of the MTC:CM4, and phallometric assessment of sexual interests toward children) in two independent samples (USA and Canada). In both samples and in relation to all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In addition to the SSPI, the phallometric method emerges as a controlled laboratory-based approach, measuring changes in penile blood volume in response to specific sexual stimuli (Cantor & McPhail, 2015;McPhail et al, 2017). For forensic assessments, the Screening Scale of Pedophilic Crime Scene Behavior (Lehmann, 2022) plays a crucial role in evaluating the behavioral aspects of sex offenders within crime scenes. Meanwhile, the Static-99R, developed by Hanson and Morton-Bourgon (2009), stands as a widely researched actuarial risk assessment tool, for predicting sexual recidivism in adult male sex offenders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the SSPI, the phallometric method emerges as a controlled laboratory-based approach, measuring changes in penile blood volume in response to specific sexual stimuli (Cantor & McPhail, 2015;McPhail et al, 2017). For forensic assessments, the Screening Scale of Pedophilic Crime Scene Behavior (Lehmann, 2022) plays a crucial role in evaluating the behavioral aspects of sex offenders within crime scenes. Meanwhile, the Static-99R, developed by Hanson and Morton-Bourgon (2009), stands as a widely researched actuarial risk assessment tool, for predicting sexual recidivism in adult male sex offenders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, men who scored a five on the SSPI were over five times more likely than those who scored a zero to exhibit greater penile responses to children than to adults ( Seto & Lalumière, 2001 ). Additional research has also suggested that the SSPI has adequate convergent validity with other measures of sexual interest in children (e.g., Banse et al, 2010 ; Dombert et al, 2017 ; Helmus et al, 2015 ; Lehmann et al, 2022 ; McPhail et al, 2020 ; Mokros et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%